2022
DOI: 10.3390/jcm11040984
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Cryoglobulinemic Vasculitis after DAA Induced HCV Cure

Abstract: Treatment with a direct acting antiviral (DAA) has revolutionized HCV therapy, as more than 95% of patients achieve a sustained virological response (SVR). Cryoglobulinemic vasculitis (CryoVas), however, can persist and recur after the HCV cure. In this systematic review, we include data from 19 studies that provided information on the persistence and recurrence of CryoVas after the HCV cure with DAAs. A complete clinical response (CR) was reported in 63.7% to 90.2% of the DAA-treated patients after achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Just recently, a large systematic review of more than 621 cases in 19 papers reported that complete remission (CR) of HCV-MCV vasculitis after achieving SVR with DAA was seen in 63.7-90.2%, while relapse was seen in 4-18%, which is considered relatively favorable. However, B-cell clonal proliferation remained in 31-40% of cases, which may have contributed to the relapse of cryoglobulinemic vasculitis ( 33 ). Serologic relapse is defined in cases with cryoglobulin >1.5%, elevated rheumatoid factor (RF), or complement 4 (C4) detected after the initial reaction ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just recently, a large systematic review of more than 621 cases in 19 papers reported that complete remission (CR) of HCV-MCV vasculitis after achieving SVR with DAA was seen in 63.7-90.2%, while relapse was seen in 4-18%, which is considered relatively favorable. However, B-cell clonal proliferation remained in 31-40% of cases, which may have contributed to the relapse of cryoglobulinemic vasculitis ( 33 ). Serologic relapse is defined in cases with cryoglobulin >1.5%, elevated rheumatoid factor (RF), or complement 4 (C4) detected after the initial reaction ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, B-cell clonal proliferation remained in 31-40% of cases, which may have contributed to the relapse of cryoglobulinemic vasculitis ( 33 ). Serologic relapse is defined in cases with cryoglobulin >1.5%, elevated rheumatoid factor (RF), or complement 4 (C4) detected after the initial reaction ( 33 ). It is thought that regular performance of these examinations may lead to the early detection of HCV-MCV vasculitis recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies showed similar outcomes [ 74 , 75 ]. On the other hand, an SVR with DAAs may improve HCV-CV symptoms at six months, but patients could relapse at one year after antiretroviral therapy [ 76 , 77 ].…”
Section: Impact Of Direct-acting Antiviral Agents On Extrahepatic Dis...mentioning
confidence: 99%
“…Relapses were detected in 4–18% of patients. Biomarkers associated with higher incidence of persistence or recurrence of CV were identified (INFL3-rs12979860, ARNTL-rs648122, RETN-rs1423096, and SERPINE1-rs6976053), but need further validation [ 70 ]. Interestingly, in a recent multicentric prospective study on data from the Italian Platform for the Study of Viral Hepatitis Therapy cohort, the authors reported self-reported clinical deterioration after an initial response in 49.6% of patients (median time of deterioration, 19 months) and that the rate of patients without any deterioration was 58% and 41% at 12 and 24 months, respectively [ 71 ].…”
Section: Impact On Extrahepatic Manifestationsmentioning
confidence: 99%